2016
DOI: 10.1186/s12889-016-3509-8
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and behavioral correlates among a nationally representative sample of school-attending adolescents in the Republic of Malawi

Abstract: BackgroundSuicide is among the top causes of adolescent mortality worldwide. While correlates of suicidal behavior are better understood and delineated in upper-income countries, epidemiologic knowledge of suicidal behavior in low-income countries remains scant, particularly in the African continent. The present study sought to add to the epidemiologic literature on suicidal behavior in Africa by examining the behavioral correlates of suicide attempts among Malawi adolescents.MethodsA cross-sectional study usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 30 publications
13
29
1
1
Order By: Relevance
“…Although causality could not be proved due to the cross-sectional nature of data, the study showed a proportional association of violence and injury experience with suicidal behavior. A previous study showed that suicide attempters had significantly higher odds of being physically bullied as well as having a serious injury among school-attending Malawi adolescents [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although causality could not be proved due to the cross-sectional nature of data, the study showed a proportional association of violence and injury experience with suicidal behavior. A previous study showed that suicide attempters had significantly higher odds of being physically bullied as well as having a serious injury among school-attending Malawi adolescents [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[10] In Malawi, a study that examined the behavioural correlates of suicide attempts among adolescents in the previous 12 months found that 7.15% of adolescents had attempted suicide at least once and that 5.75% had made two or more attempts. [16]…”
Section: Researchmentioning
confidence: 99%
“…Our results support previous studies on alcohol and drug abuse among youth. [9,[15][16] Of concern is the fact that in SA, rules and regulations regarding alcohol consumption have been in existence for some time, [12] but enactment does not appear to be producing positive outcomes. There is therefore an urgent need to review alcohol policy so that it can be effective in regulating the use of alcohol, especially by individuals aged <18 years.…”
Section: Researchmentioning
confidence: 99%
“…Externalizing problems may include, alcohol use,7,12,14,15 drug use,1315 cannabis use,16 soft drink consumption,17 being bullied,7,12,18,19 exposure to interpersonal violence,10 being physically attacked,13,15 and in physical fight,15 sexual coitus20 and injury 21. Limited data exist on the prevalence and correlates of suicide attempts among adolescents in Guatemala.…”
Section: Introductionmentioning
confidence: 99%